A novel variation in RSPO4 causing nonsyndromic congenital nail disorder-4 in a Chinese patient - Zhang, Qiang; Yang, Qi; Zhou, Xunzhao; Zhang, Sujie; Luo, Jingsi (Frontiers in Pediatrics, 2025)
BackgroundNon-syndromic congenital nail disorder type 4 (OMIM: 206800) is a rare autosomal recessive condition characterized by severe hypoplasia or complete absence of fingernails and toenails. This disorder results from variants in the RSPO4 gene (OMIM: 610573) located on chromosome 20p13.ObjectiveThis study aimed to assess the potential pathogenicity of a novel RSPO4 variant identified in a Chinese patient and to explore the phenotypic and molecular genetic characteristics of Non-syndromic congenital nail disorder type 4.MethodsWhole-exome sequencing was performed in the proband to identify candidate variants. Sanger sequencing validated the variant and determined its origin. In silico prediction tools were used to evaluate the variant's functional impact. Pathogenicity classification followed the American College of Medical Genetics and Genomics guidelines. A systematic literature review was conducted to collate previously reported cases.ResultsA novel frameshift variant in the RSPO4 gene—c.268dupA/p.Cys91fs*6—was identified and classified as likely pathogenic based on the American College of Medical Genetics and Genomics guidelines. The clinical presentation of the patient was consistent with the diagnostic criteria for Non-syndromic congenital nail disorder type 4. Literature review confirmed that Non-syndromic congenital nail disorder type 4 primarily manifests as generalized nail dysplasia without associated hair, dental, or skeletal abnormalities.ConclusionThis study expands the known genetic spectrum of Non-syndromic congenital nail disorder type 4 and enhances the understanding of phenotypic characteristics associated with RSPO4 variants. The findings have potential implications for improving variant-based screening, genetic diagnostics, and molecular insights into RSPO4-related disorders.